Shangdian xinfeng (Xuan zi Huaxian nongmin huazhan) - Cheng Minsheng,
'Fresh breeze in the shop(Selected from the Huxian peasant painting exhibition).' Printno. 8171.897. Call number: BG E27/327 is Chinese export version.